A Parallel Algorithm for Clipping Polygons with Improved Bounds and a Distributed Overlay Processing System Using MPI - Puri, Satish; Prasad, Sushil K. (2015 15th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing, 2015)
Clipping arbitrary polygons is one of the complex operations in computer graphics and computational geometry. It is applied in many fields such as Geographic Information Systems (GIS) and VLSI CAD. We have two significant results to report. Our first result is the effective parallelization of the classic, highly sequential Greiner-Hormann algorithm, which yields the first output-sensitive CREW PRAM algorithm for a pair of simple polygons, and can perform clipping in O(logn) time using O(n+k) processors, where n is the total number of vertices and k is the number of edge intersections. This improves upon our previous clipping algorithm based on the parallelization of Vatti's sweepline algorithm, which requires O(n+k+k') processors to achieve logarithmic time complexity where k' can be O(n 2 ). This also improves upon another O(logn) time algorithm by Karinthi, Srinivas, and Almasi which unlike our algorithm does not handle self-intersecting polygons, is not output-sensitive, and must employ O(n 2 ) processors to achieve O(logn) time. We also study multi-core and many-core implementations of our parallel Greiner-Hormann algorithm. Our second result is a practical, parallel GIS system, namely MPI-GIS, for polygon overlay processing of two GIS layers containing large number of polygons over a cluster of compute nodes. It employs R-tree for efficient indexing and identification of potentially intersecting set of polygons across two input GIS layers. Spatial data files tend to be large in size (in GBs) and the underlying overlay computation is highly irregular and compute intensive. This system achieves 44X speedup on a 32-node NERSC's CARVER cluster while processing about 600K polygons in two GIS layers within 19 seconds which takes over 13 minutes on state-of-art ArcGIS system.